Genetic control of glandular trichome densities and their association with whitefly resistance from Solanum galapagense accession LA1401 - Andrade, Marcela Carvalho (2015)
Tomato is affected by a large number of arthropod pests, among which the whitefly (Bemisia tabaci) is considered to be one of the most destructive. Arthropod pest management by chemical control is often inefficient. Therefore, tomato breeding programs have been trying to develop resistant cultivars by introgression of resistance present in wild species. In S. galapagense the resistance to whitefly has been associated with the presence of type IV glandular trichomes. Knowledge about the genetic control of type IV glandular trichome densities would facilitate trait introgression. Our research aimed to study the inheritance of type IV glandular trichome densities, their association with resistance to whitefly, and to identify quantitative trait loci (QTL) associated with the presence of these trichomes in populations derived from the interspecific cross Solanum lycopersicum TOM-684 x Solanum galapagense accession LA1401. High estimates for both broad and narrow sense heritabilities of type IV glandular trichome densities suggest that inheritance of this trait is not complex. Whitefly resistance was associated with high density of type IV glandular trichomes. F2 (S. galapagense x S. lycopersicum) progeny selected for high densities of type IV glandular trichomes showed similar levels of resistance to those found in LA1401, considered resistant to whitefly. Two QTLs were detected as associated with type IV trichomes: one major QTL (gal.IV-2), responsible for 35.22% of phenotypic variation, located on chromosome 2, and another minor QTL (gal.IV-3) located on chromosome 3. QTL gal.IV-2 appears to be mainly responsible for the presence of type IV trichomes in S. galapagense.